Preparation method and application of carbon fiber composite material
By employing a special electrode method combining gradient layup and conductive silver paste, the problems of electrode contact resistance and uneven heating in the self-heating curing process of carbon fiber composites were solved, enabling efficient and low-energy preparation of carbon fiber composites and improving the curing degree and mechanical properties of the products.
Patent Information
- Application Number
- CN202511457559.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-13
- Publication Date
- 2025-12-23
AI Technical Summary
In the current process of self-heating curing molding of carbon fiber reinforced polymer composites, the electrode contact resistance is too high and the heating is uneven, resulting in insufficient curing in the middle of the product, which affects the yield and mechanical properties of the product.
A special electrode method combining gradient lay-up and conductive silver paste is used to achieve the curing of carbon fiber composite materials by electrothermal heating. This is achieved by coating the stepped surface of carbon fiber prepreg with silver paste and connecting it with conductive metal to form an electrode.
This improved the temperature uniformity and heating efficiency in the electrode area, reduced the contact resistance at the prepreg end, ensured overall temperature uniformity, and enhanced the curing degree and mechanical properties of carbon fiber prepreg, enabling rapid and low-energy preparation of large-size, high-performance composite materials.
Smart Images

Figure CN121179772A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of carbon fiber reinforced polymer composite molding technology, and more specifically, to a method for preparing carbon fiber composite materials and their applications. Background Technology
[0002] Carbon fiber reinforced polymer composites (CFRP) have important applications in aerospace and other fields due to their excellent specific strength and specific stiffness.
[0003] Prepreg is a composition made by impregnating a resin matrix with reinforcing materials. It has a uniform fiber areal density and is a key intermediate material in the preparation process of carbon fiber reinforced polymer composites.
[0004] A common method for preparing carbon fiber reinforced polymer composites from prepreg is hot pressing, which involves stacking several layers of carbon fiber prepreg and then forming them using a hot press. However, hot pressing has the following problems: because it requires heating a hot plate beforehand to transfer heat to the carbon fibers, the heating and cooling process of the hot plate is lengthy, resulting in high energy consumption. Furthermore, the size of the carbon fiber reinforced polymer composite is limited by the size of the hot plate. Therefore, the cost of carbon fiber reinforced polymer composites prepared by hot pressing is very high.
[0005] Carbon fiber is an excellent conductor with a certain resistance. According to Joule's law, it generates heat when an electric current flows through it. Therefore, passing an electric current through carbon fiber can achieve heat curing and molding of carbon fiber reinforced polymer composites. This method is called Direct Electrical Curing (DEC). DEC solves the problems of high energy consumption and size limitations associated with hot pressing.
[0006] A Chinese patent discloses a controllable self-heating method for carbon fiber using a liquid molding process. Positive and negative foil electrodes are laid at both ends of a continuous carbon fiber fabric, using a multi-layered or intermittent arrangement. However, because the carbon fiber surface is coated with insulating resin, both methods result in higher contact resistance and higher temperatures in the electrode areas, while the non-electrode areas cannot uniformly and effectively conduct electricity and generate heat, resulting in lower temperatures. This further leads to sufficient curing at the electrode ends but insufficient curing in the middle of the product. Consequently, a defect-concentrated area forms in the middle of the product, leading to a decrease in yield, reduced mechanical properties, and difficulty in meeting the material performance requirements of load-bearing structures. Summary of the Invention
[0007] The purpose of this invention is to address the technical problems of high electrode contact resistance and uneven heating in the electro-thermal curing process of carbon fiber reinforced polymer composite materials in the prior art, and to provide a method for preparing carbon fiber composite materials that reduces electrode contact resistance and improves heating uniformity.
[0008] The above-mentioned objective of this invention is achieved through the following technical solution: A method for preparing a carbon fiber composite material includes the following steps: S1. Gradient layup: At least two layers of carbon fiber prepreg are laid from bottom to top, with the carbon fiber orientation direction as the length direction. The length of the N+1 layer is less than the length of the N layer, and the two ends of the N+1 layer and the N layer in the length direction are arranged in a stepped structure. S2. Electrode construction: Silver paste is coated on the stepped structure surface of each layer of carbon fiber prepreg, conductive metal is covered on the silver paste, and the conductive metal is connected to the wire to construct the electrode; S3. Molding: The electrodes are heated to a set temperature and then cured to obtain carbon fiber composite material.
[0009] The method for preparing carbon fiber composite materials of the present invention is applicable to the preparation of carbon fiber composite materials from multilayer carbon fiber prepregs, and is particularly applicable to the preparation of carbon fiber composite materials from two or more layers of carbon fiber prepregs.
[0010] In the preparation method of carbon fiber composite materials of this invention, an electro-thermal curing molding process is adopted. A special electrode combining gradient layup and conductive silver paste improves the temperature uniformity and heating efficiency in the electrode area. This effectively reduces the contact resistance at the prepreg ends, preventing overheating and scorching at the ends, and enhances the overall temperature uniformity during the electro-thermal process. It significantly improves the degree of curing, curing uniformity, and mechanical properties of the carbon fiber prepreg, enabling rapid, efficient, low-energy, and low-cost manufacturing of large-size, high-performance carbon fiber reinforced polymer composite structures. This method is particularly suitable for the construction of space and outer space facilities such as space stations, lunar bases, and Mars bases.
[0011] The method for preparing carbon fiber composite materials of the present invention adopts self-heating curing molding by electric current, which has low energy consumption and does not require large-scale hot pressing equipment compared with hot pressing method.
[0012] The method for preparing carbon fiber composite materials of the present invention is applicable to carbon fiber prepregs with rectangular structures.
[0013] In the carbon fiber prepreg of the present invention, the orientation direction of the carbon fiber is unidirectional (0° direction), that is, the carbon fiber is arranged along the length direction.
[0014] Preferably, in step S1, the distance between one end of the N+1th layer in the length direction and the same end of the Nth layer in the length direction is h, the length of the Nth layer is H, and the ratio of h to H does not exceed 0.015.
[0015] Controlling the distance between one end of the N+1th layer and the same end of the Nth layer along its length direction helps ensure that the silver paste can fully contact each layer of the carbon fiber prepreg, improving the uniformity of the overall temperature during the electric heating process, while not significantly affecting the overall dimensions of the carbon fiber composite material.
[0016] Preferably, in step S1, the ratio of h to H is 0.005 to 0.012.
[0017] Preferably, in step S1, at least four layers of carbon fiber prepreg are arranged sequentially from bottom to top. In specific embodiments, 6 to 40 layers of carbon fiber prepreg may be arranged sequentially from bottom to top, typically 10 to 20 layers.
[0018] Applying pressure to the carbon fiber prepreg during the curing process helps to eliminate potential air bubbles, enhance interlayer bonding strength, and increase the volume fraction content of carbon fiber.
[0019] Preferably, in step S3, the flexible airbag is placed on top of the carbon fiber prepreg layer and constrained, and pressure is applied to the airbag by inflation. The pressure applied to the airbag is 40~300kPa.
[0020] This invention employs airbag pressurization, which can apply high pressure exceeding 1 atmosphere to the structural molding of large-size carbon fiber prepregs, thereby improving the mechanical properties of carbon fiber composite materials and meeting the requirements for high-performance structures.
[0021] The flexible airbag is made of polyvinyl chloride.
[0022] Preferably, the airbag is inflated using an air compressor, and the compressor is turned off after the set pressure is reached. This helps reduce energy consumption.
[0023] Preferably, in step S3, pressure is applied to the carbon fiber prepreg layer using a hydraulic press, autoclave, or vacuum bag before the electrodes are heated by electricity.
[0024] High pressures can be applied using hydraulic presses or autoclaves; however, the size of these presses and autoclaves cannot be too large, limiting the maximum structural size of carbon fiber composite materials to several meters.
[0025] Vacuum bags can be used to apply pressure to large-sized carbon fiber prepreg structures, with a maximum pressure of one atmosphere (0.1 MPa).
[0026] Preferably, pressure is stopped once curing is complete. Hydraulic presses, autoclaves, or vacuum bags need to operate continuously throughout the curing process, which consumes slightly more energy than airbag pressure.
[0027] Preferably, in step S3, when the temperature reaches the set value, the control current is reduced to maintain a constant temperature, and the heating is stopped after curing is completed.
[0028] A current-temperature automated energized heating temperature control scheme can be used, which is particularly suitable for the preparation of large composite material structures.
[0029] The present invention also protects a method for repairing structurally damaged materials, comprising the following steps: placing carbon fiber prepreg on the surface of the damaged area of the structurally damaged material, coating both ends of the carbon fiber prepreg with silver paste, covering the silver paste with conductive metal, connecting the conductive metal with a wire to construct an electrode; and heating the electrode to repair the structurally damaged material.
[0030] Preferably, the structural damage material is one or more of a metallic material, a polymer material, or a composite material.
[0031] Compared with the prior art, the present invention has the following beneficial technical effects: This invention provides a method for preparing carbon fiber composite materials, employing an electro-hydraulic self-heating curing process. A special electrode combining gradient layup and conductive silver paste improves temperature uniformity and heating efficiency in the electrode area. This effectively reduces the contact resistance at the prepreg ends, preventing overheating and scorching, and enhances the overall temperature uniformity during electro-hydraulic heating. It significantly improves the degree of curing, curing uniformity, and mechanical properties of the carbon fiber prepreg, enabling rapid, efficient, low-energy, and low-cost manufacturing of large-size, high-performance carbon fiber reinforced polymer composite structures. This method is particularly suitable for the construction of space and outer space facilities such as space stations, lunar bases, and Mars bases. Attached Figure Description
[0032] Figure 1 This is a schematic diagram of the prepreg layup for comparative and example embodiments.
[0033] Figure 2 This is a photograph of the actual product after silver paste has been applied to the stepped surface of each layer of carbon fiber prepreg.
[0034] Figure 3 This is a photograph of a device after conductive metal is connected to a wire to coat a silver paste layer.
[0035] Figure 4 This is a schematic diagram of the control panel dimensions.
[0036] Figure 5 This is a diagram showing the dimensions of a polyvinyl chloride (PVC) airbag.
[0037] Figure 6 This is a schematic diagram of the pressure airbag and its restraints.
[0038] Figure 7 This is a schematic diagram of the composite material structure in Example 4.
[0039] Figure 8This is a schematic diagram showing the locations for measuring the degree of cure in Comparative Example 2 and Example 2.
[0040] Figure 9 Schematic diagram for repairing damaged aluminum alloy sheet: (a) Rectangular aluminum sheet with round hole; (b) Side view of glass fiber layer, carbon fiber layer, and aluminum alloy sheet to be repaired; (c) Electrode and wire connected to both ends of carbon fiber prepreg.
[0041] In the diagram, 1-carbon fiber prepreg, 2-silver paste, 3-copper foil. Detailed Implementation
[0042] The present invention will be further described below with reference to specific embodiments, but the embodiments do not limit the present invention in any way. Unless otherwise stated, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.
[0043] Carbon fiber / epoxy resin prepreg unidirectional tape, Weihai Guangwei, T700 grade, USN20000 / 6511KS.
[0044] Silver Glue, Deer Fairy, LZX919124.
[0045] Airbag, manufactured in Hengshui, Hebei Province, measuring 80×1200mm, made of polyvinyl chloride.
[0046] Example 1 A method for preparing a carbon fiber composite material includes the following steps: S1. Gradient layup: Six layers of rectangular unidirectional carbon fiber prepreg are laid sequentially from bottom to top, with the carbon fiber orientation direction as the length direction. The thickness of each layer of carbon fiber prepreg is 0.2 mm, and the total thickness of the carbon fiber prepreg is 1.2 mm. The width of each layer of carbon fiber prepreg is 20 mm.
[0047] The length of the Nth layer is H, and the distance between one end of the N+1th layer along the length direction and the same end of the Nth layer along the length direction is h.
[0048] The length of the first layer of carbon fiber prepreg is 100mm.
[0049] The length of the second layer of carbon fiber prepreg is 98mm. The distance between one end of the second layer in the length direction and the same end of the first layer in the length direction is 1mm. The ratio of h to H is 1 / 100 = 0.01.
[0050] The length of the third layer of carbon fiber prepreg is 96mm. The distance between one end of the third layer in the length direction and the same end of the second layer in the length direction is 1mm. The ratio of h to H is 1 / 98≈0.0102.
[0051] The length of the fourth layer of carbon fiber prepreg is 94mm. The distance between one end of the fourth layer in the length direction and the same end of the third layer in the length direction is 1mm. The ratio of h to H is 1 / 96≈0.0104.
[0052] The length of the fifth layer of carbon fiber prepreg is 92mm. The distance between one end of the fifth layer in the length direction and the same end of the fourth layer in the length direction is 1mm. The ratio of h to H is 1 / 94≈0.0106.
[0053] The sixth layer of carbon fiber prepreg is 90mm long. The distance between one end of the sixth layer in the length direction and the same end of the fifth layer in the length direction is 1mm. The ratio of h to H is 1 / 92≈0.0109.
[0054] like Figure 1 As shown in (b), the N+1th layer and the two ends of the Nth layer in the length direction are arranged in a stepped structure. S2. Coat the stepped structure surface of each layer of carbon fiber prepreg with silver paste, attach the copper foil electrode with connecting wires to the silver paste, wherein the copper foil is 10mm long and 20mm wide; connect the copper sheet to the wires to construct the electrode; S3. Molding: The electrodes are heated to a set temperature and then cured to obtain carbon fiber composite material.
[0055] Example 2 A method for preparing a carbon fiber composite material differs from that in Example 1 in that: S1. Gradient layup: Ten layers of rectangular unidirectional carbon fiber prepreg are laid sequentially from bottom to top, with the carbon fiber orientation direction as the length direction. The thickness of each layer of carbon fiber prepreg is 0.2 mm, and the total thickness of the carbon fiber prepreg is 2 mm. The width of each layer of carbon fiber prepreg is 40 mm.
[0056] The length of the Nth layer is H, and the distance between one end of the N+1th layer along the length direction and the same end of the Nth layer along the length direction is h.
[0057] The length of the first layer of carbon fiber prepreg is 200mm.
[0058] The length of the second layer of carbon fiber prepreg is 198 mm. The distance between one end of the second layer along its length and the same end of the first layer along its length is 1 mm, and the ratio of h to H is 1 / 200 = 0.005.
[0059] The length of the third layer of carbon fiber prepreg is 196 mm. The distance between one end of the third layer along its length and the same end of the second layer along its length is 1 mm, and the ratio of h to H is 1 / 198≈0.00505.
[0060] The length of the fourth layer of carbon fiber prepreg is 194 mm. The distance between one end of the fourth layer along its length and the same end of the third layer along its length is 1 mm, and the ratio of h to H is 1 / 196≈0.00510.
[0061] The length of the fifth layer of carbon fiber prepreg is 192 mm. The distance between one end of the fifth layer along its length and the same end of the fourth layer along its length is 1 mm, and the ratio of h to H is 1 / 194≈0.00515.
[0062] The sixth layer of carbon fiber prepreg is 190 mm long. The distance between one end of the sixth layer along its length and the same end of the fifth layer along its length is 1 mm, and the ratio of h to H is 1 / 192 ≈ 0.00521.
[0063] The length of the seventh layer of carbon fiber prepreg is 188 mm. The distance between one end of the seventh layer along its length and the same end of the sixth layer along its length is 1 mm, and the ratio of h to H is 1 / 190 ≈ 0.00526.
[0064] The length of the eighth layer of carbon fiber prepreg is 186 mm. The distance between one end of the eighth layer along its length and the same end of the seventh layer along its length is 1 mm, and the ratio of h to H is 1 / 188≈0.00532.
[0065] The length of the ninth layer of carbon fiber prepreg is 184 mm. The distance between one end of the ninth layer along its length and the same end of the eighth layer along its length is 1 mm, and the ratio of h to H is 1 / 186≈0.00538.
[0066] The length of the tenth layer of carbon fiber prepreg is 182 mm. The distance between one end of the tenth layer along its length and the same end of the ninth layer along its length is 1 mm, and the ratio of h to H is 1 / 184 ≈ 0.00543.
[0067] like Figure 1 As shown in (b), the N+1th layer and the two ends of the Nth layer in the length direction are arranged in a stepped structure.
[0068] The rest is the same as in Example 1, and will not be repeated here.
[0069] Example 3 A method for preparing a carbon fiber composite material includes the following steps: S1. Gradient Layup: Cut unidirectional carbon fiber prepreg strips according to ASTM / D7264 / D7264M-21 standards. Lay 16 layers of rectangular unidirectional carbon fiber prepreg strips from bottom to top, with the carbon fiber orientation direction as the length direction. Each layer of carbon fiber prepreg has a thickness of 0.2 mm, for a total thickness of 3.2 mm. Each layer of carbon fiber prepreg has a width of 13 mm.
[0070] The length of the Nth layer is H, and the distance between one end of the N+1th layer along the length direction and the same end of the Nth layer along the length direction is h.
[0071] The length of the first layer of carbon fiber prepreg is 140mm.
[0072] The length of the second layer of carbon fiber prepreg is 138 mm. The distance between one end of the second layer along its length and the same end of the first layer along its length is 1 mm, and the ratio of h to H is 1 / 140 ≈ 0.00714.
[0073] The length of the third layer of carbon fiber prepreg is 136 mm. The distance between one end of the third layer along its length and the same end of the second layer along its length is 1 mm, and the ratio of h to H is 1 / 138 ≈ 0.00725.
[0074] The length of the fourth layer of carbon fiber prepreg is 134 mm. The distance between one end of the fourth layer along its length and the same end of the third layer along its length is 1 mm, and the ratio of h to H is 1 / 136 ≈ 0.00735.
[0075] The length of the fifth layer of carbon fiber prepreg is 132 mm. The distance between one end of the fifth layer along its length and the same end of the fourth layer along its length is 1 mm, and the ratio of h to H is 1 / 134 ≈ 0.00746.
[0076] The sixth layer of carbon fiber prepreg is 130 mm long. The distance between one end of the sixth layer along its length and the same end of the fifth layer along its length is 1 mm, and the ratio of h to H is 1 / 132 ≈ 0.00758.
[0077] The length of the seventh layer of carbon fiber prepreg is 128 mm. The distance between one end of the seventh layer along its length and the same end of the sixth layer along its length is 1 mm, and the ratio of h to H is 1 / 130 ≈ 0.00769.
[0078] The length of the eighth layer of carbon fiber prepreg is 126 mm. The distance between one end of the eighth layer along its length and the same end of the seventh layer along its length is 1 mm, and the ratio of h to H is 1 / 128 = 0.0078125.
[0079] The length of the ninth layer of carbon fiber prepreg is 124 mm. The distance between one end of the ninth layer along its length and the same end of the eighth layer along its length is 1 mm, and the ratio of h to H is 1 / 126≈0.00794.
[0080] The length of the tenth layer of carbon fiber prepreg is 122 mm. The distance between one end of the tenth layer along its length and the same end of the ninth layer along its length is 1 mm, and the ratio of h to H is 1 / 124 ≈ 0.00806.
[0081] The length of the eleventh layer of carbon fiber prepreg is 120mm. The distance between one end of the eleventh layer along its length and the same end of the tenth layer along its length is 1mm, and the ratio of h to H is 1 / 122≈0.00820.
[0082] The length of the twelfth layer of carbon fiber prepreg is 118 mm. The distance between one end of the twelfth layer in the length direction and the same end of the eleventh layer in the length direction is 1 mm, and the ratio of h to H is 1 / 120≈0.00833.
[0083] The length of the thirteenth layer of carbon fiber prepreg is 116 mm. The distance between one end of the thirteenth layer along its length and the same end of the twelfth layer along its length is 1 mm, and the ratio of h to H is 1 / 118≈0.00847.
[0084] The length of the fourteenth layer of carbon fiber prepreg is 114 mm. The distance between one end of the fourteenth layer along its length and the same end of the thirteenth layer along its length is 1 mm, and the ratio of h to H is 1 / 116≈0.00862.
[0085] The length of the fifteenth layer of carbon fiber prepreg is 112 mm. The distance between one end of the fifteenth layer along its length and the same end of the fourteenth layer along its length is 1 mm, and the ratio of h to H is 1 / 114≈0.00877.
[0086] The length of the sixteenth layer of carbon fiber prepreg is 110 mm. The distance between one end of the sixteenth layer along its length and the same end of the fifteenth layer along its length is 1 mm, and the ratio of h to H is 1 / 112≈0.00893.
[0087] like Figure 1 As shown in (b), the N+1th layer and the two ends of the Nth layer in the length direction are arranged in a stepped structure.
[0088] Laying carbon fiber prepreg: Apply the prepreg onto the release fabric as follows Figure 1 The prepreg is laid layer by layer in the [0°6 / -15° / 15° / 15° / -15° / 0°6] layup pattern shown in (c); where z is the thickness direction, y is the length direction, and x is the width direction.
[0089] S2. Apply conductive silver paste evenly to the stepped areas at both ends of each layer of carbon fiber prepreg, as shown in the figure. Figure 2 As shown, ensure each step is covered with silver paste. Cover the silver paste at the prepreg end with copper foil, connect the copper foil to the wire, and construct the electrode as shown. Figure 3 As shown.
[0090] S3. Place the laid carbon fiber prepreg in a position such as... Figure 4 The worktable with perforated steel sheet shown.
[0091] On the worktable, place a rigid PET polyester plastic sheet as a waterproofing cloth, absorbent felt, and release cloth in sequence. Place the carbon fiber prepreg layer on the release cloth, and then cover it with another layer of release cloth. Attach the positive and negative copper foils of the DC power supply to the copper foils at both ends of the layer to construct a closed circuit.
[0092] Airbag compression: Figure 5 The airbag shown (1m in length and 10cm in diameter) is connected to an air compressor and a pressure gauge. The airbag is placed on top of the carbon fiber prepreg layer and secured to the platform using ropes or cable ties through holes in the worktable. It is then inflated using the air compressor, with the pressure adjusted to 160kPa. The inflation time is 2 minutes. Figure 6 As shown, once the set pressure is reached, the air compressor is turned off.
[0093] Regulating Power Supply for Heating and Curing: Constructing an automated power-on heating temperature control device. A Mitsubishi PLC is used as the main control unit; a DC power supply and a thermocouple temperature sensor are connected via an RS485 communication interface; an adaptive current control program is designed using the GXworks2 software platform; and a temperature feedback closed-loop control mechanism is implemented. The Mitsubishi FX3U, DC power supply, and thermocouple temperature measuring instrument are connected via the Modbus RS485 communication protocol. The PLC reads the temperature and issues commands to adjust the current of the DC power supply. The required temperature for prepreg curing is input into the control program, and the real-time temperature is read by the thermocouple probe and input into the PLC system for comparison. When the actual temperature reaches the set minimum value, the PLC automatically controls the current to decrease, and the system automatically starts a heat preservation timer for 15 minutes. After the timer ends, the system automatically reduces the current and shuts off the power, terminating the heating process.
[0094] Cooling and demolding: Maintain pressure and wait for the sample temperature to drop below 50°C before demolding. Figure 7 The carbon fiber composite structural component product shown.
[0095] Example 4 A method for repairing structurally damaged materials includes the following steps: The material causing the structural damage was a 6061 aluminum alloy sheet with dimensions of 160mm×30mm×2mm and a 10mm opening in the middle.
[0096] Four layers of carbon fiber prepreg fabric were used as the repair patch, with the overall dimensions of the patch being 40mm × 30mm × 0.8mm (4 layers in total). (1) such as Figure 9As shown in (a), first select a 6061 aluminum alloy sheet with a 10mm diameter hole in the center and perform necessary pretreatment to ensure that the surface of the aluminum sheet is clean and free of impurities and oil stains, so as to ensure the subsequent repair effect.
[0097] (2) such as Figure 9 As shown in (b), the glass fiber layer is first adhered to the circular hole as an insulation layer. Then, four layers of carbon fiber prepreg are evenly adhered to the surface of the glass fiber layer as a repair patch, ensuring that the prepreg completely covers the gap area.
[0098] (3) such as Figure 9 As shown in (c), silver paste is applied to both ends of the carbon fiber repair patch, and wires and copper electrodes are attached to both ends of the carbon fiber repair patch respectively. The electrodes are fixed in the predetermined position by copper foil tape.
[0099] (4) Turn on the DC power supply and observe the temperature with a thermal imager. When the temperature of the carbon fiber repair sheet reaches 120°C, keep it warm for 15 minutes and cool it to room temperature; complete the repair of the damaged material.
[0100] Comparative Example 1 like Figure 1 As shown in (a), a method for preparing a carbon fiber composite material includes the following steps: S1. Layup: Six layers of rectangular unidirectional carbon fiber prepreg are laid sequentially from bottom to top, with the carbon fiber orientation direction as the length direction. The thickness of each layer of carbon fiber prepreg is 0.2 mm, and the total thickness of the carbon fiber prepreg is 1.2 mm. The width of each layer of carbon fiber prepreg is 20 mm. The length of each layer of carbon fiber prepreg is 100 mm.
[0101] S2. Attach the copper foil electrode with connecting wires to both ends of the topmost (sixth layer) prepreg, wherein the copper foil is 10mm long and 20mm wide; connect the copper sheet to the wires to construct the electrode; S3. Molding: The electrodes are heated to a set temperature and then cured to obtain carbon fiber composite material.
[0102] Comparative Example 2 like Figure 1 As shown in (a) above, a method for preparing a carbon fiber composite material differs from Comparative Example 1 in that: S1. Ten layers of rectangular unidirectional carbon fiber prepreg are arranged sequentially from bottom to top, with the carbon fiber orientation direction as the length direction. The thickness of each layer of carbon fiber prepreg is 0.2 mm, and the total thickness of the carbon fiber prepreg is 2 mm. The width of each layer of carbon fiber prepreg is 40 mm. The length of each layer of carbon fiber prepreg is 200 mm.
[0103] S2. Attach the copper foil electrode with connecting wires to both ends of the top layer (tenth layer) of prepreg, wherein the copper foil is 10mm long and 20mm wide; connect the copper sheet to the wires to construct the electrode; S3. Molding: The electrodes are heated to a set temperature and then cured to obtain carbon fiber composite material.
[0104] Comparative Example 3 A method for preparing a carbon fiber composite material includes the following steps: S1. Cut unidirectional carbon fiber prepreg strips according to ASTM / D7264 / D7264M-21 standards. Arrange 16 layers of rectangular unidirectional carbon fiber prepreg strips from bottom to top, with the carbon fiber orientation direction as the length direction. Each layer of carbon fiber prepreg has a thickness of 0.2 mm, for a total thickness of 3.2 mm. Each layer of carbon fiber prepreg has a width of 13 mm and a length of 110 mm.
[0105] Laying carbon fiber prepreg: Apply the prepreg onto the release fabric as follows Figure 1 The prepreg is laid layer by layer in the [0°6 / -15° / 15° / 15° / -15° / 0°6] layup pattern shown in (c); where z is the thickness direction, y is the length direction, and x is the width direction.
[0106] S2. Cover the end of the prepreg with copper foil and connect the copper foil to the wire.
[0107] Place the laid carbon fiber prepreg on the molding worktable.
[0108] Lay out the impermeable fabric, absorbent felt, and release fabric in sequence.
[0109] Apply the vacuum bag to the molding worktable using vacuum adhesive, covering the entire prepreg to be cured, and then apply a vacuum; adjust the pressure to 90 kPa.
[0110] Power supply adjustment for temperature rise and curing: A Mitsubishi FX3U processor, a DC power supply, and a thermocouple temperature measuring instrument are connected via Modbus RS485 communication protocol. The PLC reads the temperature and issues commands to adjust the DC power supply current. The required curing temperature for the prepreg is input into the control program. Real-time temperature is then read via the thermocouple probe and compared with the PLC system. When the actual temperature reaches the set minimum value, the system automatically starts a 15-minute holding timer. After the timer expires, the system automatically reduces the current and shuts off the power.
[0111] Cooling and demolding: Maintain pressure and wait for the sample temperature to drop below 50°C before demolding to obtain the desired product.
[0112] Result detection The resistance of the carbon fiber prepregs of Examples 1-2 and Comparative Examples 1-2 was measured, and the temperature at the electrodes and the middle of the prepregs was recorded during the heating process.
[0113] (1) Contact resistance, temperature and curing degree tests: The degree of cure was obtained by differential scanning calorimetry. The location diagram for the degree of cure test is shown below. Figure 8 As shown.
[0114] Table 1
[0115] Table 2
[0116] As can be seen from Tables 1 and 2, when copper foil was directly applied to the ends of the carbon fiber prepreg in Comparative Examples 1 and 2, the heating temperature was extremely uneven. The temperature rise at the electrodes of the prepreg was too high, while the middle section had difficulty heating. The temperature rise at both ends of the prepreg was always significantly higher than that in the middle, resulting in good curing only at the ends of the prepreg, while the middle section was almost uncured. Figure 8 As shown in (a) of Comparative Example 2, the degree of curing of carbon fiber prepreg regions ① and ② is less than 18%, and due to local heat concentration and excessively high temperature, the resin at one end electrode is scorched.
[0117] In the prepregs of Embodiments 1 and 2 of this invention, the temperature is more uniform, and the heating rate in the middle section is closer to that at both ends of the prepreg, allowing the prepreg to rapidly reach the curing temperature as a whole. Figure 8 As shown in (b) of Example 2, the degree of curing of the carbon fiber prepreg in regions ③ and ④ exceeds 95%.
[0118] The contact resistance of Comparative Example 1 is significantly higher than that of Example 1. Higher resistance results in higher DC power output energy consumption. This demonstrates that the method of the present invention can reduce energy consumption.
[0119] This demonstrates that the invention employs a special electrode combining gradient layup and conductive silver paste, which improves the temperature uniformity and heating efficiency of the electrode area. This effectively reduces the contact resistance at the prepreg tip, preventing overheating and scorching in the tip area, and enhances the overall temperature uniformity during the heating process. Consequently, it significantly improves the curing degree, curing uniformity, and mechanical properties of the carbon fiber prepreg, ultimately yielding a high-performance composite material.
[0120] (2) Bending strength: The test standard is ASTM standard ASTM / D7264 / D7264M-21.
[0121] Carbon fiber mass fraction: The test method is calculation based on the difference in weight. The higher the carbon fiber mass fraction, the better the mechanical properties of the composite material.
[0122] The bending strength test was performed four times, the average value was taken, and the standard deviation was calculated.
[0123] Table 3
[0124] As can be seen from Comparative Example 3, vacuum bag pressing can only provide one atmosphere of pressure (≈100 kPa), while the pressure applied by the airbag in Example 3 of this invention is 160 kPa. At higher pressures, the electrode contact resistance can be reduced. With the same sample size, the fiber mass fraction and flexural strength of the sample prepared by airbag pressing are higher than those prepared by vacuum bag pressing, and the standard deviation of the data is smaller, indicating fewer dangerous defects in the sample. This demonstrates that the sample prepared by airbag pressing has higher mechanical properties. Furthermore, this invention uses airbag pressing, and the pressure range can be 40~300 kPa, which can be adjusted according to actual needs.
[0125] (5) The tensile strength of the Al-6061 aluminum alloy sheet repaired in Example 4 is shown in Table 4 below.
[0126] Table 4
[0127] As shown in the table above, the electrothermal heating method described in this invention can rapidly cure carbon fiber prepreg, thus enabling its application in the rapid repair of damaged materials. For Al-6061 aluminum alloy, the tensile strength repair effect is 73.89%~80.89%. This method is not limited to the repair of damaged metallic materials, but can also be used for polymer materials, composite materials, etc.
[0128] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing carbon fiber composite material, characterized in that, Includes the following steps: S1. Gradient layup: At least two layers of carbon fiber prepreg are laid from bottom to top, with the carbon fiber orientation direction as the length direction. The length of the N+1 layer is less than the length of the N layer, and the two ends of the N+1 layer and the N layer in the length direction are arranged in a stepped structure. S2. Electrode construction: Silver paste is coated on the stepped structure surface of each layer of carbon fiber prepreg, conductive metal is covered on the silver paste, and the conductive metal is connected to the wire to construct the electrode; S3. Molding: The electrodes are heated to a set temperature and then cured to obtain carbon fiber composite material.
2. The method for preparing carbon fiber composite material according to claim 1, characterized in that, In step S1, the distance between one end of the N+1th layer in the length direction and the same end of the Nth layer in the length direction is h, the length of the Nth layer is H, and the ratio of h to H does not exceed 0.
015.
3. The method for preparing carbon fiber composite material according to claim 2, characterized in that, In step S1, the ratio of h to H is 0.005~0.
012.
4. The method for preparing carbon fiber composite material according to claim 1, characterized in that, In step S1, at least four layers of carbon fiber prepreg are sequentially arranged from bottom to top.
5. The method for preparing carbon fiber composite material according to claim 1, characterized in that, In step S3, the flexible airbag is placed on top of the carbon fiber prepreg layer and constrained, and pressure is applied to the airbag by inflation. The pressure applied to the airbag is 40~300kPa.
6. The method for preparing carbon fiber composite material according to claim 5, characterized in that, The airbag is inflated using an air compressor until the set pressure is reached, then the air compressor is turned off.
7. The method for preparing carbon fiber composite material according to claim 1, characterized in that, In step S3, pressure is applied to the carbon fiber prepreg layer using a hydraulic press, autoclave, or vacuum bag, and then the electrodes are heated by electricity.
8. The method for preparing carbon fiber composite material according to claim 7, characterized in that, Once curing is complete, stop applying pressure.
9. A method for repairing structurally damaged materials, characterized in that, The steps include: placing carbon fiber prepreg on the surface of the damaged area of the structurally damaged material, coating both ends of the carbon fiber prepreg with silver paste, covering the silver paste with conductive metal, and connecting the conductive metal to the wire to construct the electrode. By applying electricity to the electrodes and heating them, the material with structural damage can be repaired.
10. The method for repairing structurally damaged materials according to claim 9, characterized in that, The material causing structural damage is one or more of the following: metallic materials, polymeric materials, or composite materials.
